Development of GeoGebra-Assisted Digital Learning Media for Geometry Transformation Materials based on Van Hiele's Theory - Asnawi, Muhammad Hasan; Turmudi, Turmudi; Harini, Sri (International Journal on Emerging Mathematics Education, 2022)
AbstractThis research aims to develop valid, practical and effective digital learning media. This development research method is Research and Development (R&D) with the ADDIE development model. The development of this digital learning media produces products in the form of android applications (apk) and websites that can be used via mobile phones or computers. The research process begins by analyzing the problems that exist in the learning process in schools. Then proceed with determining and preparing the design of the learning media. The collected materials were then developed into learning media with the help of GeoGebra, Ispring, Android Studio, and Notepad++. Then validation was carried out by media experts, material experts, learning experts, and practitioners and field trials were given to high school students in class XI. In the preparation of this learning media, it follows van Hiele's theory to be adapted to the stages of students' thinking about geometry. Based on the results of the validation and field trials, the digital learning media that have been developed meet the valid, practical, and effective criteria for use in classroom learning